Advanced Trainer. Six Practice Tests with Answers - O'Dell F. Felicity (Cambridge English)
SIX PRACTICE TESTS WITH ANSWERS. Advanced trainer is preparation companion for the revised Cambridge English: Advanced, also known as Certificate in Advanced English (CAE) It combines exam practice with easy-to-follow expert guidance, and exam tips designed to guarantee exam success. The first two tests are fully guided, with tips and advice on how to tackle each paper Additional grammar, vocabulary and writing practice activities help students avoid typical mistakes made by real exam candidates in Cambridge English: Advanced Answer key includes clear explanations and model answers for the Writing paper Audio for the listening and speaking test activities is available online for download 'Without answers' version also available, plus Audio CDs with the listening and speaking test activities for both versions.